Chemical Composition, Antioxidant and Antimicrobial Activities of Essential Oil from Leutea kurdistanica mozaff - Naser Karimi; Iraj Salimikia*; Parvin Ramak; Zhaleh Soheilikhah; Mohammad Shamizadeh; Mohammad Bagher Gholivand (Lorestan University of Medical Sciences, 2016)
Background and Aim: Leutea kurdistanica mozaff. (Apiaceae) is a perennial herb endemic to Kurdistan province of Iran. The plants of this family are known for diversity in essential oils and economic importance. The goals of the present study were to evaluate chemical composition, antioxidant and antimicrobial activities of essential oils of L. kurdistanica. Materials and Methods: GC-FID and GC-MS were used for compositional analysis of the essential oils.Antioxidant activities of the oil were assessed using DPPH free radical test. Antibacterial and antifungal activities of the oils were assessed by disc diffusion and agar dilution methods. Results: A total of 33 compounds representing 97.3-94.2% of the essential oils were identified. Limonene (25.3%) was the main compound of the oil followed by γ-terpinene (18.1%), elemicin (15.4%) and Δ-3-carene (8.2%). In DPPH assay, the oil has radical scavenging activity with IC50 value of 51.4±2.3. The results of antimicrobial tests showed that the oil had remarkable inhibitory effects on the growth of Gram-positive bacteria and fungal strains. Conclusions: Regarding to significant antioxidants and antimicrobial activities of the oil of L. kurdistanica, these oils could be consider as a natural preservative in food and other industries. Although more investigation is needed to clarify the exact compounds responsible for observed biological activities.